Precursor of amyloid protein in Alzheimer disease undergoes fast anterograde axonal transport. - Koo, E H (1990)
In the brains of aged humans and cases of Alzheimer disease, deposits of amyloid in senile plaques are located in proximity to nerve processes. The principal component of this extracellular amyloid is beta/A4, a peptide derived from a larger amyloid precursor protein (APP), which is actively expressed in brain and systemic organs. Mechanisms that result in the proteolysis of APP to form beta/A4, previously termed beta-amyloid protein, and the subsequent deposition of the peptide in brain are unknown. If beta/A4 in senile plaques is derived from neuronally synthesized APP and deposited at locations remote from sites of synthesis, then APP must be transported from neuronal cell bodies to distal nerve processes in proximity to deposits of amyloid. In this study, using several immunodetection methods, we demonstrate that APP is transported axonally in neurons of the rat peripheral nervous system. Moreover, our investigations show that APP is transported by means of the fast anterograde component. These findings are consistent with the hypothesis of a neuronal origin of beta/A4, in which amyloid is deposited in the brain parenchyma of aged individuals and cases of Alzheimer disease. In this setting, we suggest that APP is synthesized in neurons and delivered to dystrophic nerve endings, where subsequent alterations of local processing of APP result in deposits of brain amyloid.